Transformational Leadership In Organizational Change - Abdul Sahid; Indriati Amirullah; Khaeriyah Khaeriyah; Nurasia Natsir; Syafaruddin Syafaruddin (International Journal of Economics and Management Research, 2023)
Leadership plays a very important role in organizational dynamics and change. This article discusses the concept, role, and emphasis on transformational leadership in the context of organizational change. Transformational leadership is an approach that allows leaders to influence and bring about positive change in an organization. This concept brings about more than just procedural changes; it creates an inspiring vision, motivates subordinates, and encourages innovation in order to achieve higher organizational goals. In this research, we explain how transformational leadership plays a central role in managing organizational change. We discuss how transformational leaders are able to create organizational cultures that support change, identify barriers, and managing resistance with a collaborative approach. We also highlight strategies used by transformational leaders to motivate team members, encourage active participation, and achieve success in the face of complex change. This study provides deeper insight into how transformational leadership can be the key to success in facing the challenges of organizational change. We explore the positive impact of transformational leadership on organizational culture, team performance, innovation and achievement of organizational goals. The findings of this research provide practical implications for leaders and managers in managing organizational change effectively. Transformational leadership is a relevant and important concept in the context of organizational change.